Work value orientations and patterns: A comparison of future managers with manager and non-manager groups - Beggs, Joyce (International journal of value-based management, 1995)
This study uses the Values for Working questionnaire to classify the primary value systems and value patterns of 501 senior business school students (future managers). The students' scores on six value systems measured by the questionnaire are compared to national data on blue collar and clerical workers and on managerial and professional workers. The business students scored in the average range for four of the six value systems when compared to the manager group, but for only one of the value systems when compared to the non-manager group. Of the business students who had a primary value system, 82 percent wereexistential ormanipulative. There were significant differences in the value systems scores by sex but not by business major.